(untitled) (Research, Society and Development, 2022)
Active Methodologies are potentialities that contribute to the teaching and learning processes, dynamizing the pedagogical practice in general, providing a space for mediation of knowledge, where the student is able to actively build their knowledge. In this sense, the student becomes the central pillar in the construction of their learning, organizing their ideas in advance, through an inverted classroom, or learning a theoretical content subsidized through gamification, which makes it even more fun. The data collection method is attenuated in an integrative literature review, as it allows the author to evaluate the scientific-academic works from a qualitative perspective, integrating their subjectivities in the research. The results allow us to systematize, based on the analyzed articles, a discussion that includes perception of Basic Education teachers about the use of Active Methodologies; the development of Active Methodologies in Basic Education and educational pedagogical paradigms; Specifics about the Flipped Classroom and a successful experience in Basic Education. Therefore, several researches are innovating the scientific literature with reviews, case studies and experience reports with emphasis on Active Methodologies, however, they need to be even more used in the educational scenario, as it allows knowledge to be surrounded by the mediation of the teacher and active in the construction of students’ knowledge, phenomena that directly meet with meaningful learning.